Development of a portable electroanalytical system for the stripping voltammetry of metals: Determination of copper in acetic acid soil extracts - Beni, V.; Ogurtsov, V.; Bakunin, N.; Arrigan, Damien; Hill, M. (Elsevier BV, 2005)
The development, characterisation and evaluation of a prototype portable electrochemical trace metal analyser are presented. The instrument is a battery-powered microcontroller-based potentiostat, which implements anodic stripping voltammetry (ASV) at suitable sensor electrodes. It is capable of operating away from the laboratory, in the absence of an external power source and is usable by low-skilled personnel. The distinguishing feature of the instrument is its custom software, which enables sample pre-screening, data processing and sample dilution and standard additions calculations to be carried out. The instrument has been evaluated by application of a methodology for the detection of copper in acetic acid soil extracts, both in the laboratory and in the field. Underpotential deposition staircase anodic stripping voltammetry (UPD-SCASV) of the copper at gold disk electrodes was used as a test method. There was good agreement between the instrument results and those from laboratory-based reference analytical methods for analyses carried out both in the laboratory and in the field.